Agricultural Efficiency in Nepal - Parajuli, Mahesh (Himalayan Review, 2011)
Not available. Key words: Agricultural; CDP; Nepal The Himalayan Review Vol. XVI, 1985 Page: 15-28 Uploaded Date: 19 April, 2011